Efektivitas Mediasi Dalam Penyelesaian Sengketa Ekonomi Syariah Di Pengadilan Agama Batang Indonesia Pada 2019-2024 - Annur, Nabhan Naufal; Hadiati, Teti (el hisbah Journal of Islamic Economic Law, 2025)
This study examines the effectiveness of mediation in resolving Islamic economic disputes at the Batang Religious Court during 2019–2024. As an institution authorized to adjudicate such disputes, the court handled eight cases, five of which were successfully resolved through mediation while three proceeded to judgment. The mediation success rate reached approximately 62.5%, indicating its significant role as a faster and more efficient dispute resolution mechanism compared to litigation. Using an empirical juridical method and a qualitative approach, this study provides an analytical description of mediation practices based on Supreme Court Regulation (PERMA) No. 1 of 2016 on Court Mediation Procedures. The results show that mediation was conducted in accordance with the regulation, with an average completion time of 1–3 months. Mediation success was influenced by mediator competence, party attendance, facilities, and public legal awareness. However, several obstacles were identified, including party absenteeism, emotional tension, and limited understanding of mediation. Cultural values of deliberation and familial harmony supported the mediation process, although they were not always effective in disputes involving financial interests. Overall, mediation at the Batang Religious Court is considered flexible, low-cost, and satisfactory for disputing parties, although improvements in facilities and public education are still needed to enhance its effectiveness.